Annual Report, 2016 - Kansas State University; University of Illinois; United States Agency for International Development (My University, 2017)
The Feed the Future Innovation Lab for the Reduction of Post-Harvest Loss (PHLIL) is a strategic, applied, research and education program aimed at improving food security by reducing post-harvest loss and food waste of seeds and durable staple crops, e.g., grains, oilseeds, and legumes. The Lab’s efforts are focused in four Feed the Future countries: Bangladesh, Ethiopia, Ghana, and Guatemala. Projects in each country are led by Country Team Co-Leaders and overseen by a U.S. Principle Investigator (PI) and the Lab’s Director, with input from local and international academic, private sector, governmental and non-governmental organizations.
Feed the Future Innovation Lab for the Reduction of Post-Harvest Loss. October 1, 2015 - September 30, 2016
Keywords: USAID; Innovation Lab; Post-Harvest Loss; Food Waste; Durable Staple Crops; Crop Seeds